Effect of Platelet-rich Plasma on Caspase-3 and IGF-1 mRNA expression in the diabetic rat testis - Evi Istiqamah; Dicky Moch. Rizal; Ika Puspitasari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
Testicular damage is a serious complication of diabetes mellitus resulting in male infertility, which is associated with caspase-3 and IGF-1 mRNA expression. Platelet-rich plasma (PRP), with its rich growth factor composition, has proven beneficial in regenerative therapy. It is believed that PRP has not been studied in testes for diabetes mellitus and there are no studies in the literature concerning the influence of PRP on expressions of growth factors in testes.The aim of this study was to investigate the efficacy of adjunctive PRP in insulin treatment for repair of testicular damage in a diabetic rat model. Diabetes was induced by administering single dose 60 mg/kg streptozotocin. Twenty Wistar male rats were divided into four groups: group 1, control group; group 2, diabetes without treatment; group 3, diabetes with treated insulin; and group 4, diabetes with treated insulin and PRP. Rats were euthanized after two weeks of treatment, and testes were taken for caspase-3 and IGF-1 mRNA expression measurements.Diabetes mellitus induction caused a significant increase in caspase-3 mRNA expression with p=0.049 and significant decrease in IGF-1 mRNA expression with p=0.004. There was no difference in caspase-3 and IGF-1 mRNA expression of the diabetic rat testis given insulin and PRP compared to without PRP.